The THE EFFECT OF PLYOMETRIC KNEE TUCK JUMP AND DEEPTH JUMP EXERCISES ON INCREASING LEG MUSCLE EXPLOSIVE POWER OF CLUB VEGAS BALLOLLY ATHLETES, 50 CITY DISTRICT - Aditra herdian; Muhammad Sazeli Rifki; Alimuddin; Donal Syafrianto (Jurnal IKEOR, 2023)
Abstract : Volleyball players in Kub Vegas, 50 City Regency, had poor explosive power in this study’s issue area. The purpose of this study is to assess the influence of knee tuck jump and deep jump training on developing the explosive power of the leg muscles of volleyball players in Kub Vegas, 50 City District. This study design may be classified as "quasi-experimental." During the months of September and October of 2023, researchers gathered data at the Kub Vegas volleyball court of the 50 City Regency. The 18 participants in this research were selected from among the 18 volleyball players at City Regency Kub Vegas. Purposive sampling was utilized, and 10 athletes were chosen at random to participate in the research. This study’s tool was a vertical jump evaluation. The t test or mean difference analysis is used to analyze the data. Based on the findings of the t test analysis, tcount > ttable (6.51 > 1.83). Significant evidence supports the veracity of the suggested research idea. The explosive strength of the leg muscles of the Kub Vegas 50 City Regency volleyball players is influenced by the knee tuck leap and the deep jump, leading to an average rise of 13.9 points. Keywords: Volleyball, Plyometric, explosive power